Linear singularly perturbed problems with pulse influence - Mel'nik, T. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish the closeness of solutions of a linear singularly perturbed problem with asymptotically large pulse influence and the corresponding degenerate problem.